2011
DOI: 10.1007/s10152-011-0257-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of macroalgal identity on epifaunal assemblages: native species versus the invasive species Sargassum muticum

Abstract: Seaweeds are a refuge from stressful conditions associated with life on rocky intertidal shores, and there is evidence that different macrophytes support different assemblages of mobile epifauna. Introduction of nonindigenous macroalgae may have a great impact on associated epifaunal assemblages and ecosystem processes in coastal areas. Previous studies have reported conflicting evidences for the ability of epifauna to colonize nonindigenous species. Here, we analyzed epifaunal assemblages associated with thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 50 publications
5
22
0
Order By: Relevance
“…This finding agrees with those described for other introduced seaweeds, suggesting that, while macroalgal invasions strongly affect diversity of sessile assemblages (Ribera and Boudouresque 1995, Piazzi et al 2001, Schaffelke and Hewitt 2007, Baldacconi and Corriero 2009, Zuljevic and Nikolic 2008, the effects of invasions on mobile organisms are more related to changes in the structure of assemblages (Vázquez-Luis et al 2009, Gestoso et al 2012, Janiak et al 2012, Pacciardi et al 2011, Engelen et al 2013. Differences between invaded and non-invaded beds were not evident five months after the disappearance of L. lallemandii.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This finding agrees with those described for other introduced seaweeds, suggesting that, while macroalgal invasions strongly affect diversity of sessile assemblages (Ribera and Boudouresque 1995, Piazzi et al 2001, Schaffelke and Hewitt 2007, Baldacconi and Corriero 2009, Zuljevic and Nikolic 2008, the effects of invasions on mobile organisms are more related to changes in the structure of assemblages (Vázquez-Luis et al 2009, Gestoso et al 2012, Janiak et al 2012, Pacciardi et al 2011, Engelen et al 2013. Differences between invaded and non-invaded beds were not evident five months after the disappearance of L. lallemandii.…”
Section: Discussionsupporting
confidence: 81%
“…Epifaunal assemblages associated with C. crinita were characterized by high abundance and diversity, compared with those described for other seaweed habitats (Gestoso et al 2012, Janiak et al 2012, Engelen et al 2013. Macroalgal assemblages associated with Mediterranean Cystoseira beds are well known (Boudouresque 1972, Sales and Ballesteros 2010), while epifaunal assemblages have been less investigated and knowledge is limited to particular taxa (Arrontes and Anadon 1990, Chemello and Milazzo 2002, Fraschetti et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…McKenzie and Moore (1981) recorded a total of 77 species, while in our study, considering Syllids alone, we reported a total of 33 species. Gestoso et al (2012) comparing the epifaunal assemblages in native and invasive seaweed species found mostly gastropods (45 % of the total taxa), polychaetes and ophiuroids in S. polyschides.…”
Section: Syllids Assemblages and Relationships With Environmental Facmentioning
confidence: 99%
“…The impacts of non-native macroalgae on fauna have been difficult to generalise as they vary in direction and magnitude depending on a number of factors, e.g. the species in question, where it is growing, and the time of year (Wernberg et al, 2004;Buschbaum et al, 2006;Lutz et al, 2010;Gestoso et al, 2012;Engelen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%